Three New Alpha1-Antitrypsin Deficiency Variants Help to Define a C-Terminal Region Regulating Conformational Change and Polymerization - Fra, Anna M.; Gooptu, Bibek; Ferrarotti, Ilaria; Miranda, Elena; Scabini, Roberta; Ronzoni, Riccardo; Benini, Federica; Corda, Luciano; Medicina, Daniela; Luisetti, Maurizio; Schiaffonati, Luisa (PLOS ONE, 2012)
Alpha1-antitrypsin (AAT) deficiency is a hereditary disorder associated with reduced AAT plasma levels, predisposing adults to pulmonary emphysema. The most common genetic AAT variants found in patients are the mildly deficient S and the severely deficient Z alleles, but several other pathogenic rare alleles have been reported. While the plasma AAT deficiency is a common trait of the disease, only a few AAT variants, including the prototypic Z AAT and some rare variants, form cytotoxic polymers in the endoplasmic reticulum of hepatocytes and predispose to liver disease. Here we report the identification of three new rare AAT variants associated to reduced plasma levels and characterize their molecular behaviour in cellular models. The variants, called Mpisa (Lys259Ile), Etaurisano (Lys368Glu) and Yorzinuovi (Pro391His), showed reduced secretion compared to control M AAT, and accumulated to different extents in the cells as ordered polymeric structures resembling those formed by the Z variant. Structural analysis of the mutations showed that they may facilitate polymerization both by loosening ‘latch’ interactions constraining the AAT reactive loop and through effects on core packing. In conclusion, the new AAT deficiency variants, besides increasing the risk of lung disease, may predispose to liver disease, particularly if associated with the common Z variant. The new mutations cluster structurally, thus defining a region of the AAT molecule critical for regulating its conformational state.